Polemicness and agonality of discourse of love: philosophical and cultural view - V. E. Turenko, (Ukrainian Cultural Studies, 2019)
The article conceptualizes the idea of the unity of love and war based on the mythological, cultural, and philosophical aspects. The author, based on a number of theoretical and empirical arguments, hypothesizes that the "polemical" (warlike) Eros`s image as archer with arrows has its roots in Middle Eastern (Sumerian-Akkadian, Semitic) mythology, which saw not the opposition of love and war, and a close relationship of these phenomenons in the image of Ishtar (Inanna, Astarte). It is highlighted that the courtly culture of love through the idea of winning lady's heart is characterized by the fact that it is the cultural, empirical embodiment of the understanding of the unity of the discourse of love and the discourse of war. It emphazises the idea that the philosophical aspect of understanding this issue is associated with two phenomenons, namely power and gift. Accordingly, it is within the frame- work of the discourse of love that the “admiration” takes place, the effect of which is explained by the fact that having subjugated the object of love, the subject himself obeys him. At the same time, in the context of the gift, there is an “agon”, that is, a competition between those in love regarding the exchange of gifts and pleasures. Therefore, it is argued that the discourse of love is polemical and agonal.
Keywords: love, love discourse, war, battle, admiration, courtly love, gift, polemicness, agonality, Eros